Representasi Nilai-Nilai Pendidikan Toleransi Antar Umat Islam dalam Film My Name Is Khan (Analisis Semiotika Roland Barthes): - Zakiah, Risalatu; Haromaini, Ahmad; Azhari, Ainul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Intra-Muslim social conflict is still an ongoing problem in the midst of community life, characterized by the gap between tolerance that appears on the surface and the low ability to solve problems substantively. Departing from this condition, this study attempts to uncover the hidden meaning behind the representation of tolerance in the film My Name Is Khan (2010). This study aims to: (1) identify and analyze the representation of educational values ​​of tolerance among Muslims in the film My Name Is Khan through an analysis of Roland Barthes's semiotic system which includes denotation, connotation, and myth; and (2) reveal and explain the manifestation of educational values ​​of tolerance among Muslims contained in the film. This study uses a qualitative descriptive approach with a library research type. Data collection techniques are carried out through non-participant observation and documentation. The data processing and analysis techniques use content analysis combined with Roland Barthes's semiotic analysis, with the analysis units being scenes, scenes, narratives, and symbols contained in the film. The results of the study show that from the 5 scenes selected based on their relevance to the values ​​of tolerance education among Muslims, five classifications of values ​​were found, namely: (1) Strong Family Establishment, (2) Strong Establishment, and (3) Solidarity. These findings indicate that the film My Name Is Khan significantly represents the values ​​of tolerance education that can be used as a learning medium in building awareness and strengthening brotherhood amidst the dynamics of Muslim life. Intra-Muslim social conflict is still an ongoing problem in the midst of community life, characterized by the gap between tolerance that appears on the surface and the low ability to solve problems substantively. Departing from this condition, this study attempts to uncover the hidden meaning behind the representation of tolerance in the film My Name Is Khan (2010). This study aims to: (1) identify and analyze the representation of educational values ​​of tolerance among Muslims in the film My Name Is Khan through an analysis of Roland Barthes's semiotic system which includes denotation, connotation, and myth; and (2) reveal and explain the manifestation of educational values ​​of tolerance among Muslims contained in the film. This study uses a qualitative descriptive approach with a library research type. Data collection techniques are carried out through non-participant observation and documentation. The data processing and analysis techniques use content analysis combined with Roland Barthes's semiotic analysis, with the analysis units being scenes, scenes, narratives, and symbols contained in the film. The results of the study show that from the 5 scenes selected based on their relevance to the values ​​of tolerance education among Muslims, five classifications of values ​​were found, namely: (1) Strong Family Establishment, (2) Strong Establishment, and (3) Solidarity. These findings indicate that the film My Name Is Khan significantly represents the values ​​of tolerance education that can be used as a learning medium in building awareness and strengthening brotherhood amidst the dynamics of Muslim life.